2018
DOI: 10.1111/joss.12437
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions and other influencing factors about monosodium glutamate in the United States

Abstract: Monosodium glutamate (MSG) is a flavor enhancer commonly used in processed food products. However, its usage is controversial in the United States. This work aimed to understand the U.S. consumers’ perception about MSG and the factors influencing their attitudes. A survey questionnaire was developed based on a focus group study and then distributed in three geographical areas in the United States. Our results showed that U.S. consumers in general had a somewhat negative attitude toward MSG. Consumer's concern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…There were 14 features about chicken soup products that were tested (Appendix A). Majority of them were from claims of commercial products and from the results of our previous study [7]. Consumers were asked to answer three questions for each feature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 14 features about chicken soup products that were tested (Appendix A). Majority of them were from claims of commercial products and from the results of our previous study [7]. Consumers were asked to answer three questions for each feature.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, substances that are naturally rich in umami components have the potential to replace MSG in food products. Wang and Adhikari found that consumers preferred natural extracts such as yeast extract, mushroom extract, and tomato extract as MSG substitute in chicken soup products [7]. Yeast typically has around 7–12% of RNA content which makes it a good source to produce nucleotide-rich ingredients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study surveyed 347 participants across the United States about their natural judgement of different types of MSG alternatives and their willingness to have them in chicken soup (Wang & Adhikari, ). Yeast extract and the extract of mushroom, tomato, and kelp were the top choices and then selected as potential categories of MSG alternative in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of these benefits, using MSG in food products is controversial in western cultures. Wang and Adhikari () reported that U.S. consumers had a somewhat negative attitude toward MSG and about 60% of respondents indicated that they have either tried to avoid or limit MSG intake. To meet consumer demands, more and more food manufacturers are removing MSG from their products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation